2022
DOI: 10.1007/s00497-022-00443-6
|View full text |Cite
|
Sign up to set email alerts
|

Repair of DNA double-strand breaks in plant meiosis: role of eukaryotic RecA recombinases and their modulators

Abstract: Homologous recombination (HR) during meiosis is crucial for the DNA double-strand breaks (DSBs) repair that promotes the balanced segregation of homologous chromosomes and enhances genetic variation. In most eukaryotes, two recombinases RAD51 and DMC1 form nucleoprotein filaments on single-stranded DNA generated at DSB sites and play a central role in the meiotic DSB repair and genome stability. These nucleoprotein filaments perform homology search and DNA strand exchange to initiate repair using homologous te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 309 publications
0
30
0
Order By: Relevance
“…However, more recent work in budding yeast and mouse suggested that RAD51 and DMC1 homofilaments do load on both DSB ends resulting in mixed recombinase filaments [2123]. This mixed recombinase filament organization has been reconstituted in vitro [24] and has thus become the favored model for recombinase loading [16, 17, 2327]. The RAD51/DMC1-DNA nucleoprotein filament is the active molecular species in searching for and invading a homologous DNA template by the 3’-ended DNA strand(s) [16, 17, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, more recent work in budding yeast and mouse suggested that RAD51 and DMC1 homofilaments do load on both DSB ends resulting in mixed recombinase filaments [2123]. This mixed recombinase filament organization has been reconstituted in vitro [24] and has thus become the favored model for recombinase loading [16, 17, 2327]. The RAD51/DMC1-DNA nucleoprotein filament is the active molecular species in searching for and invading a homologous DNA template by the 3’-ended DNA strand(s) [16, 17, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…This mixed recombinase filament organization has been reconstituted in vitro [24] and has thus become the favored model for recombinase loading [16,17,[23][24][25][26][27]. The RAD51/DMC1-DNA nucleoprotein filament is the active molecular species in searching for and invading a homologous DNA template by the 3'-ended DNA strand(s) [16,17,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations